An acoustic method for the determination of dispersivecomposition of organic suspensions - Stanisław SZYMA (Archives of Acoustics)
In this paper it is shown that the sedimentation analysis of an organic suspension can be made rapidly using ultrasonic methods in which an ultrasonic plane wave is used to induce very rapid sedimentation of the dispersed phase, while a transversal ultrasonic wave is used to determine the course of the changing concentration of the dispersed phase during sedimentation in the ultrasonic field. A description of the measuring system as well as results of experimental studies for determining the dispersive composition of some organic suspensions are given.